GASTRODUODENAL FISTULA DUE TO PEPTIC ULCER - Ataseven, H.; Celebis; Yalniz, M.; Gunaydin, S.; Poyrazoglu, O. K.; Bahcecioglu, I. H. (Aves, 2007)
Gastroduodenal fistula, a short accessory canal extending from the distal stomach to the duodenal bulb, is a rare condition. To date, about 100 cases have been reported in the literature. Presumably, the intramural penetration of an ulcer in the antrum creates adhesions between the stomach and duodenum. We present an unusual case of perforation of a giant gastric ulcer at the angular notch into the duodenum with formation of a large, persistent fistula.
Keywords: Gastroduodenal fistula; peptic ulcer; NSAID